Heritable pulmonary arterial hypertension complicated by multiple pulmonary arteriovenous malformations. (2021) - Arano, Takahiro; Imamoto, Takuro; Suda, Rika; Kasai, Hajime; Sugiura, Toshihiko; Shigeta, Ayako; Yamamoto, Keiko; Nagata, Jun; Sakao, Seiichiro; Tanabe, Nobuhiro; Tatsumi, Koichiro
Abstract: Heritable pulmonary arterial hypertension (HPAH) is a type of familial pulmonary arterial hypertension, while pulmonary arteriovenous malformations (PAVMs) are abnormal communications between pulmonary arteries and veins that occur frequently in patients with hereditary hemorrhagic telangiectasia (HHT). A 21-year-old woman on continuing medication for HPAH was hospitalized. She had been diagnosed with HPAH at age 4 years and had been receiving epoprostenol infusion from age of 9 years. Although lung perfusion scintigraphy showed a shunt fraction of 18.9% at age of 19 years, the cause of the shunt was unclear. At the time of the present hospitalization, enhanced computed tomography (CT) of the chest and four-dimensional reconstructed images revealed multiple abnormal communications between the peripheral pulmonary arteries and veins. Furthermore, right heart catheterization revealed an elevated mean pulmonary arterial pressure. Wedged angiography of the pulmonary artery of the right lower lobe revealed several PAVMs. Multiple PAVMs and suspected HHT with HPAH was diagnosed. The possibility of PAVMs should be considered even in patients with HPAH. Moreover, evaluation of the shunt fraction by lung perfusion scintigraphy and morphological examination of PAVM by contrast-enhanced CT may facilitate PAVM detection in patients with HPAH